Чернігів у творчій спадщині Євгенії Спаської - Луговик, Т. (Сiверянський лiтопис, 2016)
У статті схарактеризовано подорожі Є. Ю. Спаської до Чернігова, з’ясовано роль та місце визначного гончарного осередку в науково-музейній спадщині дослідниці. В статье, ссылаясь на дневниковые записи Евгении Юрьевны Спасской, рассмотрены все ее посещения г. Чернигова, охарактеризовано впечатление исследовательницы от путешествий, показаны место и роль Чернигова в научно-исследовательском наследии выдающегося этнографа. In the article investigated the ethnographic tour E.Yu Spassky to Chernihiv to collect samples of pottery-tiled production. Special attention is devoted to research and study E.Yu Spassky crafts of our land. Article can trace the topographical features of the last century in Chernihiv and Chernihiv condition pottery of the late nineteenth and early twentieth centuries. The study found materials about the development of the museum case of our city. It was found the role and place of Chernihiv as important pottery center of left-bank Ukraine, particularly in the creative and scientific heritage known researcher of folk art.